2010
DOI: 10.3109/08039488.2010.489954
|View full text |Cite
|
Sign up to set email alerts
|

Identifying co-occurring substance use disorders in community mental health centres. Tailored approaches are needed

Abstract: The CMHCs participating in this study lack sufficient diagnostic routines and specific instruments to identify SUD. Clinical research that relies on methods used in this study will need combined approaches to provide reliable findings. Both clinical practice and research would benefit from valid, reliable screening methods and diagnostic procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 178 publications
0
14
0
Order By: Relevance
“…In a recent study of CMHCs in Norway, we found that only 10% of the patients had received ICD-10 diagnoses [14] of SUD [15]. The obvious explanation was under-detection by the clinicians.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study of CMHCs in Norway, we found that only 10% of the patients had received ICD-10 diagnoses [14] of SUD [15]. The obvious explanation was under-detection by the clinicians.…”
Section: Introductionmentioning
confidence: 99%
“…2006). The scale has good convergent (Wüsthoff et al 2011) as well as face validity, directly asking “Please rate your use of cannabis in the past 1 month according to the following scale: 0=”no use” to 5=”almost daily.” A urine sample was screened for the presence of tetrahydrocannabinol (THC cutoff 50 ng/mL) utilizing Instant Technologies iCup (Norfolk, VA). The rapid drug screen has detection times up to one month and is commonly used in drug research (McRae-Clark et al 2013).…”
Section: To the Editormentioning
confidence: 99%
“…This scale is among the most widely used in UHR programs (Buchy et al, 2015; Woods et al, 2009) and found to be highly reliable in psychosis populations (ICCs≥.93; Brunette et al, 2006). The scale has good convergent (Wusthoff et al, 2011) as well as face validity, directly asking “Please rate your use of cannabis in the past 1 month according to the following scale: 0 = “no use” to 5 = “almost daily.”…”
Section: Methodsmentioning
confidence: 99%